Utility of platelet count and platelet indices as a prognostic indicator in pregnancy induced hypertension - Saini, Neha; Gautam, Roli; Jeyaseelan, Shanti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Changes in the hemostatic system are observed in both normal and hypertensive pregnant patients. Although the exact pathophysiology of pregnancy induced hypertension is not completely understood, numerous pathophysiological mechanisms, alone or in combination, have been suggested to be responsible for the diverse subsets of PIH. Methods: This was a prospective case control study conducted on 100 pregnant females (50 PIH and 50 normotensive) at Holy Family Hospital, New Delhi, from October 2020 to May 2021. platelet count and platelet indices (mean platelet volume and ratio of platelet count to mean platelet volume) at 32 weeks and at time of delivery were checked and Outcomes were compared. Results: For predicting PIH, platelet count showed sensitivity of 82% and specificity of 54%, MPV sensitivity of 54% and specificity of 82%, PC/MPV sensitivity of 82% and specificity of 62%. For predicting pre-eclampsia without severe symptoms, platelet count showed sensitivity of 89.47% and specificity of 47.62%, mean platelet volume sensitivity of 47.37% and specificity of 76.19%, platelet count/mean platelet volume sensitivity of 31.58% and specificity of 100%. We also found that in predicting pre-eclampsia with severe symptoms platelet count showed a sensitivity of 100% and specificity of 26.32%, whereas, mean platelet volume showed equal sensitivity and specificity of 55.56%, platelet count/mean platelet volume with sensitivity of 44.44% and specificity of 84.21%. Conclusions: We found that platelet count and platelet count/mean platelet volume decreases while mean platelet volume increases with severity of pregnancy induced hypertension.